2013
DOI: 10.1002/clen.201300287
|View full text |Cite
|
Sign up to set email alerts
|

Bio‐Struvite: A New Route to Recover Phosphorus from Wastewater

Abstract: The ability of selected bacteria: Myxococcus xanthus, Bacillus pumilus, Halobacterium salinarum, and Brevibacterium antiquum to produce phosphorus bio‐mineral in settled wastewater and sludge dewatering centrifuge liquors was investigated. B. pumilus and B. antiquum were capable of growing and producing bio‐minerals identified as struvite that reached up to 250 µm in size within ten days. This study opens a completely new route to remove and recover phosphorus as struvite from wastewater, with advantages such … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
30
2
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 16 publications
1
30
2
1
Order By: Relevance
“…Brevibacterium antiquum (DSM 21545) was purchased from the German Resource Centre for Biological Material (Braunschweig, Germany). Starter cultures were grown in B41 synthetic media (4 g/L of yeast extract, 2 g/L of magnesium sulphate heptahydrate, and 2 g/L of dipotassium hydrogen phosphate), incubated in conical flasks, at room temperature (20-22°C), under agitation at 150 rpm (Stuart SSL1, Fisher Scientific, Loughborough, UK) for 4 days [6].…”
Section: Microorganism and Cultivation In Sludge Dewatering Liquorsmentioning
confidence: 99%
See 3 more Smart Citations
“…Brevibacterium antiquum (DSM 21545) was purchased from the German Resource Centre for Biological Material (Braunschweig, Germany). Starter cultures were grown in B41 synthetic media (4 g/L of yeast extract, 2 g/L of magnesium sulphate heptahydrate, and 2 g/L of dipotassium hydrogen phosphate), incubated in conical flasks, at room temperature (20-22°C), under agitation at 150 rpm (Stuart SSL1, Fisher Scientific, Loughborough, UK) for 4 days [6].…”
Section: Microorganism and Cultivation In Sludge Dewatering Liquorsmentioning
confidence: 99%
“…Inoculation of sludge dewatering liquors was done with B. antiquum cells centrifuged (Sanyo MSE Falcon 6/300 centrifuge, 2400g, 5 min) from starter cultures and resuspended in the same volume of autoclaved 0.9% NaCl aqueous solution, in order to avoid the addition of PO 4 , NH 4 -N and Mg 2+ present in the B41 media to the sludge dewatering liquors [6]. In all the experiments, the sludge dewatering liquors were sterilized by autoclaving at 121°C for 20 min after controlling the pH to obtain a post-autoclave pH of 7.8.…”
Section: Microorganism and Cultivation In Sludge Dewatering Liquorsmentioning
confidence: 99%
See 2 more Smart Citations
“…The precipitation of phosphorus in wastewater treatment systems in the form of struvite is of great interest, since it can remove phosphorous and the precipitated mineral can be sold, which gives additional value to wastewater treatment processes (Marti et al 2010;Soares et al 2013). On the other hand, it has been reported that precipitation of calcium carbonate minerals, such as calcite or vaterite, is one of the factors that drive the fouling of membrane processes ).…”
mentioning
confidence: 99%